International Tourism and The COVID-19 Pandemic: The Use of Virtual Reality to Increase Tourism Destination Sustainability and How Users Perceive The Authenticity of VR Experiences - Gegung, Eunike M (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
This paper aims to analyze the use of virtual reality (VR) in the wake of the COVID-19 pandemic to increase destination sustainability and to explore the authenticity of VR experiences as a substitute for real-life experiences. It begins by giving a brief background of the effect of the COVID 19 crisis on the tourism industry. Then archival research or document review is used to collect the data, it may, therefore, be analyzed through a thematic and content analysis. This paper showed VR is considered as a viable instrument to promote the sustainability of tourist destinations not only from an environmental and cultural perspective but also the economic aspect of host communities through the development of alternate forms of income. Promoting the use of VR may mitigate the possibility of virus spreading, increase destination sustainability and provide another option for a wider audience of visitors to see how prospective and worthy the sites are.